Channel quality information (CQI) reporting algorithms in LTE-A - Ahamad Sukor, Masturah; Mohd. Ramli, Huda Adibah (Medwell Publishing, 2016)
Corresponding modulation and coding scheme will be selected by evolved Node B (eNodeB) through amplitude modulation and coding according to Channel Quality Information (CQI). This CQI is measured and estimated by User Equipment (UE) before being feedback to the eNodeB. In this study, the automated CQI reporting algorithm, the average CQI reporting algorithm and average RB-based (resource block) CQI reporting algorithm are being compared to see which algorithm is better in terms of producing reliable channel. The simulation results show that the average CQI reporting algorithm produced more compromising results than the automated CQI reporting algorithm and the average RB-based CQI reporting algorithm